If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5(y + 3) + 6y = 7 Reorder the terms: 4 + -5(3 + y) + 6y = 7 4 + (3 * -5 + y * -5) + 6y = 7 4 + (-15 + -5y) + 6y = 7 Combine like terms: 4 + -15 = -11 -11 + -5y + 6y = 7 Combine like terms: -5y + 6y = 1y -11 + 1y = 7 Solving -11 + 1y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 1y = 7 + 11 Combine like terms: -11 + 11 = 0 0 + 1y = 7 + 11 1y = 7 + 11 Combine like terms: 7 + 11 = 18 1y = 18 Divide each side by '1'. y = 18 Simplifying y = 18
| 2(3x-4)=3(2x+1)-11 | | 1/1/k | | 16v-81v^3= | | y=-3/2*2-3 | | y=-3/2*3-3 | | 49y^2+42y+9= | | y=-7/10(-7)+7 | | 1/3y-1/4y=1/y^2 | | 78.1%147= | | 2x-9=7x+4 | | 10x^2+6x-99=0 | | 10x^2+6x-99=100 | | 4y^2+3/2y-2=0 | | 7x^2-5=100 | | 235-5x=40x+20 | | 21p+52=10 | | 5/(2w+12)+1=-8/(w+6) | | 3x+36=10x-41# | | 7/w-2=-8+(5/w+1) | | 6x/x+1+2/x-3=6 | | 12r+24=-12 | | x^2-5x+22=0 | | 16-9u=20 | | 3x+3(x-2)+3= | | (-3)-(-2)+(-1)(-1)(2)= | | (4y+1)(8-y)=0 | | x^2+25x+20=0 | | 5d+-25=-75 | | 6x+56=14x | | 3x+72=12x | | (x-2)(4x+5)=9 | | 45-15=-10m |